Workspirit six Vitra. new. (Vitra (International) AG : Birsfelden, 1998)
Ambasz, Emilio ; Ando, Tadao ; Arad, Ron ; Bellini, Mario ; Berngne, Sebastian ; Citterio, Antonio ; Eames, Charles & Ray ; Foster, Norman ; Gehry, Frank O. ; Grimshaw, Nicholas ; Hadid, Zaha ; Meda, Alberto ; Morrison, Jasper ; Nelson, George ; Panton, Verner ; Santachiara, Denis ; Van Severen, Maarten ; Siza, Alvaro ; Starck, Philippe
boek